Improving Photovoltaic Performance of Hybrid Organic-Inorganic MAGeI3 Perovskite Solar Cells via Numerical Optimization of Carrier Transport Materials (HTLs/ETLs) - Tariq AlZoubi; Bachar Mourched; Mahmoud Al Gharram; Ghaseb Makhadmeh; Osama Abu Noqta (Nanomaterials, 2023)
In this study, a hybrid organic–inorganic perovskite solar cell (PSC) based on methylammonium germanium triiodide (MAGeI3), which is composed of methylammonium (<semantics>CH3N<msubsup>H3+</msubsup>)</semantics> cations and germanium triiodide (<semantics>Ge<msubsup>I3−</msubsup></semantics>) anions, has been numerically studied using SCAPS-1d codes. An extensive investigation of various electron transport layers (ETLs) and hole transport layers (HTLs) was conducted to identify the most optimal device configuration. The FTO/ZnOS/MAGeI3/PEDOT-WO3 structure performed the highest efficiency of all combinations tested, with an impressive optimized efficiency of 15.84%. This configuration exhibited a Voc of 1.38 V, Jsc of 13.79 mA/cm2, and FF of 82.58%. J-V characteristics and external quantum efficiency (EQE) measurements indicate that this device offers superior performance, as it has reduced current leakage, improved electron and hole extraction characteristics, and reduced trap-assisted interfacial recombination. Optimum device performance was achieved at active layer thickness of 560 nm. These findings may also serve as a basis for developing lightweight and ultra-thin solar cells, in addition to improving overall efficiency. Furthermore, a comprehensive correlation study was conducted to evaluate the optimum thickness and doping level for both ZnOS-ETL and PEDOT-WO3-HTL. The photovoltaic performance parameters of the FTO/ZnOS/MAGeI3/PEDOT-WO3 structure were analyzed over a wide temperature range (275 K to 450 K). The structure exhibited stable performance at elevated operating temperatures up to 385 K, with only minimal degradation in PCE of approximately 0.42%. Our study underscores the promise of utilizing cost-effective and long-term stability materials like ZnOS and PEDOT-WO3 alongside the toxic-free MAGeI3 perovskite. This combination exhibits significant potential for eco-friendly PSC, paving the way for the development of highly efficient ultra-thin PSC.